2020
DOI: 10.3390/polym12020453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Na2CO3 on the Microstructure and Macroscopic Properties and Mechanism Analysis of PVA/CMC Composite Film

Abstract: Polyvinyl alcohol (PVA)/carboxyl methyl cellulose sodium (CMC)/Na2CO3 composite films with different contents of Na2CO3 were prepared by blending and solution-casting. The effect of Na2CO3 on the microstructure of PVA/CMC composite film was analyzed by Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry (DSC), and atomic force microscopy (AFM). Its macroscopic properties were analyzed by water sorption, solubility, and dielectric constant tests. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…1a. The neat PVA/CMC membrane displayed a sharp reflection at 2θ = 20°, corresponding to the (101) lattice planes of PVA and semi crystalline nature of CMC [78,100]. An additional peak appeared at 2θ = 12.1°for nanoclay loaded membrane corresponds to the reflection from (001) plane of halloysite nanoclay [32].…”
Section: Resultsmentioning
confidence: 96%
“…1a. The neat PVA/CMC membrane displayed a sharp reflection at 2θ = 20°, corresponding to the (101) lattice planes of PVA and semi crystalline nature of CMC [78,100]. An additional peak appeared at 2θ = 12.1°for nanoclay loaded membrane corresponds to the reflection from (001) plane of halloysite nanoclay [32].…”
Section: Resultsmentioning
confidence: 96%
“…According to Zhu et al [70], pure PVA exhibited low dielectric constant, and the increase in the dielectric constant was observed for PVA/ CMC composite film.…”
Section: Properties Of Pva/cmc Compositesmentioning
confidence: 95%
“…According to this study, the cross-linked PVA-based composite could provide a good balance between the salt rejection and the permeate flux under lower operating pressure. Tajeddin et al [69] also reported the water absorption of 22.03 percent for PVA/CMC blend film prepared by the casting method after 24 h. Zhu et al [70] stated that the pure PVA film had low water sorption and it enhanced by adding CMC to the composite film. This was reported to be due to the blending of two different molecule types resulting in the structure deformation and making more hydrophilic networks.…”
Section: Properties Of Pva/cmc Compositesmentioning
confidence: 99%
“…The Whatman membranes are fabricated using borosilicate glass and the main peak of the FTIR spectra in this study is due to BO 4 at 1031 cm −1 . [ 31 ] When the battery is cycled, the peaks belonging to Na 2 CO 3 , [ 32 ] SiC, and CO and CH 2 bonds are present for all environmental temperatures. The turquoise‐colored region of peaks is due to ClO 4 − , C=O, OH, and NaClO 4 phases.…”
Section: Resultsmentioning
confidence: 99%